EuReCa_Srbija 2014-2021 - Analysis of data on non-initiation of CPR in relation to the age of patients with VBSZ - VasiliC, Milica; Bandulaja, Marina; Susković Bosancic, Rajka; Medic, Sara; Ristic, Jovana (Journal Resuscitatio Balcanica, 2024)
Objectives: Sudden out-of-hospital cardiac arrest represents a significant public health issue as the third leading cause of death worldwide. The annual incidence of OHCA in Europe ranges between 67 and 170 cases per 100,000 inhabitants, although it is believed that the actual number might be higher. Despite the measures taken and the attention drawn to the importance of this issue, both among healthcare professionals and the general population, the survival rate remains below 10%. Early recognition of cardiac arrest, initiation of CPR, and early defibrillation significantly improve survival and long-term outcomes in survivors of OHCA. Materials and Methods: The study included epidemiological data on OHCA collected through the European Resuscitation Council's EuReCa study questionnaires, covering the period from October 1, 2014, to December 31, 2021. Variables are presented as frequencies and percentages. Analytical statistical steps included the Chi-square test to examine the association between categorical variables and the Fisher exact probability test.Results: A total of 8,349 OHCA cases were recorded during the observed period. Out of that number, CPR was initiated in 2,758/8,349 cases (33.1%). A statistically significant difference was observed depending on the age group of the patients (χ2 (3) = 225.376; p
Keywords: CPR; OHCA; epidemiology OHCA; age and OHCA